The incursion of Leviathan: Wartime territorial control and post-conflict state capacity in Peru - Guillermo Kreiman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
How do civil war dynamics affect state-building decisions in the aftermath of conflict? This paper argues that, in the post-conflict period, the state focuses its efforts to build state capacity on areas in which state power has been eroded during wartime, with the goal of avoiding future insurgent threats. Using the Peruvian civil war as the case of study and relying on a difference-indifferences design employing data for the period 1961-2007, I show that contested and insurgentcontrolled districts were targeted with the deployment of state bureaucrats after the end of the conflict, while only rebel-held territories improved their level of public goods and services provision. Results are complemented by anecdotal qualitative evidence and remain robust across several robustness checks. These findings contribute to a better understanding of the interrelation between state capacity and civil war, highlighting the potential state-building effects of internal armed conflicts.
Keywords: D74; N46; 330; civil war; state capacity; post-conflict; insurgency; Peru